How to address virtual teamwork in SMEs by an innovative co-design platform. (19th January 2011) - Germani, Michele; Mengoni, Maura; Peruzzini, Margherita
Collaborative product development is crucial for extended enterprises in order to promote innovation facing market competitiveness. Co-design software platforms aim at facilitating companies networking to achieve common design goals. A successful cooperation depends on tools' ability to effectively manage communication, data sharing in distributed teams and specific interaction requirements. In the context of small and medium enterprises (SMEs), the integration of design and supply chains is not a trivial task. Their highly flexible organisation makes difficult to manage multidisciplinary teamwork and advanced co-design software implementation. This paper presents a structured method for defining an innovative co-design platform for SMEs. System architecture can be defined by applying suitable metrics based on collaborative process characteristics in order to assess functionalities performance of available tools. Benchmarking is based on different levels of collaboration recognised in typical SMEs product development process. Correlation between process metrics, software functionalities and specific collaboration needs is managed by adopting quality function deployment (QFD) techniques.